Communication and culture an introduction - Schirato, Tony; Yell, Susan (Sage Publications, 2000)
"From Saussure to Bourdieu, from Freud to Fouclault, this book outlines a range of theoretical approaches to the study of communication and culture. Concepts are introduced in everyday particular contexts to demonstrate the essential skills of textual analysis. The book focuses on three 'primary' systems of communication: spoken, written and visual. Examples are chosen from contemporary popular culture and common social and cultural practices in a range of media, including newspapers, magazines, television, film, politics, internet discussions and ordinary speech." "Readership: students of media and communication studies, sociology and cultural studies."